The Potential of Flora and Fauna as Tourist Attractions in Biodiversity Park of Pelawan Forest, Central Bangka - Henri Henri; Luchman Hakim; Jati Batoro (Biosaintifika: Journal of Biology & Biology Education, 2017)
Indonesia has a high potential for the diversity of flora and fauna species together with their ecosystem. Preservation of natural resources can be done through conservation using the concept of ecotourism. The purpose of this research is to identify the potential of the flora and fauna in Biodiversity Park of Pelawan Forest for tourist attraction. The study was conducted from October 2016 to January 2017 through inventory and in-depth interview. The analysis on the results of this study indicate that there are 41 species of 27 families of plants and 135 species of animals consisting of amphibians (6 species), reptiles (16 species), birds (99 species) and mammals (14 species). This indicates that Biodiversity Park of Pelawan Forest is very competitive for tourism attractions, which is supported by the presence of key species (Tristaniopsis merguensis), flagship species (Cephalopachus bancanus), and abundance of birds for bird watching. Based on the IUCN red list, several species of flora, such as Gonystylus bancanus, and fauna, such as Setornis criniger, Chloropsis sonnerati, Macaca nemestrina, Nycticebus menagensis, and Cephalopachus bancanus, are vulnerable to extinction. This study on flora and fauna results in the initial data that can be used to support conservation efforts. Moreover, the result of this study can provide an opportunity for visitors to enjoy these tourist attractions, which can benefit the local community.